1998
DOI: 10.1021/js9703481
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of lonic Strength on Liposome–Buffer and 1-Octanol–Buffer Distribution Coefficients

Abstract: The distribution of salmeterol and proxicromil between unilamellar vesicles of dioleoylphosphatidylcholine (DOPC) and aqueous buffer at pH 7.4 has been studied, using an ultrafiltration method, as a function of compound concentration, DOPC concentration, and buffer ionic strength. The binding of these ionized lipophilic compounds to neutral DOPC vesicles induces a surface charge, which causes the observed membrane distribution coefficient D(mem)obs to vary significantly with bound compound to DOPC ratio and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 31 publications
2
55
0
1
Order By: Relevance
“…Ion pairing was also excluded because the apparent D mw varied at fixed ionic strength with the concentration of drug. The ion pair formation accounted for no more than 5 % of the overall partitioning of the anionic drug proxicromil [132].…”
Section: Ion Pair Formation At the Membrane Interphasementioning
confidence: 97%
See 2 more Smart Citations
“…Ion pairing was also excluded because the apparent D mw varied at fixed ionic strength with the concentration of drug. The ion pair formation accounted for no more than 5 % of the overall partitioning of the anionic drug proxicromil [132].…”
Section: Ion Pair Formation At the Membrane Interphasementioning
confidence: 97%
“…The ion pair of pentachlorophenoxide (PCP À ) with Li þ partitions about half a log-unit preferentially into octanol than the ion pair with Na þ or K þ , both of which form about equally strong ion pairs [129]. Moreover, the acidic drug proxicromil exhibited ion pair partitioning that was threefold higher with Li þ than with Na þ [132]. Experiments of ion pair formation of PCP À with divalent counter-ions Mg 2þ and Ca 2þ suggest that a 2:1 complex of PCP À and M 2þ is formed, most likely in the form of MPCP þ with PCP À as a counter-ion [129].…”
Section: Octanol-water Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the 'propranolol-sodium lauryl sulfate complex' provided promising sustained drug delivery and were feasible to be encapsulated in microparticles for a more sustained drug release effect. Austin et al (1998) studied the distribution of salmeterol and proxicromil between unilamellar vesicles of dioleoylphosphatidylcholine (DOPC) and aqueous buffer at pH 7.4, using an ultrafiltration method, as a function of compound concentration, DOPC concentration, and buffer ionic strength. The binding of these ionized lipophilic compounds to neutral DOPC vesicles induces a surface charge, which causes the observed membrane distribution coefficient D (mem)obs to vary significantly with bound compound to DOPC ratio and with ionic strength.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Na partição de compostos contendo grupos ionizáveis ou permanentemente carregados, encontram-se trabalhos explorando outros aspectos importantes para a partição, como os efeitos das variações da concentração do composto, dos volumes das fases (Dearden & Bresnen, 1988;Andrés et al, 2015), da temperatura (Brooke et al, 1986), da força iônica (Austin et al, 1998;Wenlock et al, 2011), de mudanças nos valores de pH utilizando tampões (Avdeef, 2001;Malvezzi & Amaral, 2010) e verificando as possibilidades de formação de par iônico (Takacs-Novak & Szasz, 1999;Koufopoulou et al, 2006;Darwish et al, 2015). Este último aspecto é de grande importância, por exemplo, nos casos em que é observado um aumento da lipofilicidade devido à possível formação do par iônico.…”
Section: O Coeficiente De Partição De Compostos Permanentemente Carreunclassified